Barriers to prevention of cervical cancer in the city of Porto Velho, Rondônia, Brazil - Daiana Evangelista Rodrigues; Kátia Fernanda Alves Moreira; Tathiane Souza de Oliveira
Objective.Identify the related factors with the no adhesion of women in preventive practices of cervical cancer (CC), in a coverage area of a Family Health Team in the city of Porto Velho (Rondônia, Brazil). Methods. Descriptive, cross-sectional study held in 2013. It was applied a questionnaire containing questions related to the health belief model (HBM) of the instrument "Champion's Health Belief Model Scale", validated and culturally adapted to Brazil, to 286 women. Results. 87.7% of women state that they have been submitted to prevention of CC; Regarding the parameters of the HBM, it was found that 74.5% of the women had low scores for the perception of susceptibility to the disease; equal percentage of women had an moderate perception of severity; 52.8% have an moderate perception of the benefits gained from the examination of prevention; and 51.4% have moderate perception of barriers to perform the same test. Conclusion. the process involving the prevention of CC involves the supply of services and availability of skilled professionals. However, the adoption of preventive behavior depends not only on external factors, but also own subjective factors to women.